The Influence of Firm Size, Profitability, and Solvency on Dividend Policy in BEI-Listed Property Companies (2019-2023) - Sirait, Enrique Christoper Jeremias; Butar-Butar, Hotlan; Melianna, Saur (PT Aksara Indo Rajawali, 2025)
This study examines the influence of firm size, profitability, and solvency on dividend policy in property and real estate companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The independent variables include firm size (proxied by the natural logarithm of total assets), profitability (measured by return on assets/ROA), and solvency (measured by debt-to-equity ratio/DER). The dependent variable is dividend policy, represented by the dividend payout ratio (DPR). Using purposive sampling, 11 companies met the criteria, resulting in 55 observations over a five-year period. Multiple linear regression analysis was employed to test the hypotheses. The findings reveal that profitability has a significant positive effect on dividend policy (β = 1.476, p = 0.014), while firm size and solvency show no significant individual effects. However, collectively, the three variables have a significant influence on dividend policy (F = 3.567, p = 0.020). The model explains 12.5% of dividend policy variation, indicating that other factors such as liquidity, growth opportunities, and regulatory environment also play essential roles in dividend decisions within the Indonesian property and real estate sector.